1999
DOI: 10.1007/s005860050194
|View full text |Cite
|
Sign up to set email alerts
|

Does bracing affect self-image? A prospective study on 54 patients with adolescent idiopathic scoliosis

Abstract: IntroductionAs brace treatment of idiopathic scoliosis has proven effective and has become accepted as a realistic treatment alternative [11], the psychological impact of its use on children has become a major concern. The psychosocial effect of bracing has been discussed in many reports. The studies have focused on children's ability to cope with the stress of chronic disability [5,10,14,17,19], on the longterm effect of scoliosis treatment, either by brace or operation [1,2,4,6,12], and on identifying factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
42
2
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 15 publications
(21 reference statements)
7
42
2
3
Order By: Relevance
“…Comparing the findings of the present study with those of other studies employing normal matched control groups, other studies do not find significant differences between the control groups and treated patients, especially in relation to brace-treated patients and controls [14,17,[24][25][26]. They do not find self-image to be adversely influenced by brace treatment in comparison to a normal control group.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Comparing the findings of the present study with those of other studies employing normal matched control groups, other studies do not find significant differences between the control groups and treated patients, especially in relation to brace-treated patients and controls [14,17,[24][25][26]. They do not find self-image to be adversely influenced by brace treatment in comparison to a normal control group.…”
Section: Discussioncontrasting
confidence: 51%
“…The instrument comprises seven domains: pain (questions 1, 2, 3,6,8,11,18), general self-image (questions 5, 14, 15), function from back condition (questions 7, 12, 13), general level of activity (questions 4, 9, 10), post-treatment self-image (questions 19,20,21), posttreatment function (questions 16,17), and satisfaction with the treatment (questions 22,23,24); each of these domains can be evaluated independently and/or by summarizing all questions in a total outcome score.…”
Section: Methods and Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…The present study did not, however, establish a causal relationship for these findings. Another recent study [36] showed that brace wearing did not affect the self-image during the treatment of adolescents with idiopathic scoliosis, except in patients with low scores for relations with family.…”
Section: Discussionmentioning
confidence: 93%